Política pública de gratuidad: un análisis de la democratización del acceso a la educación superior en Ecuador, período 2006-2015 (Estudios) - Mesías Tamayo, Rita Alexandra (2024)
This study identifies the effect of the public policy implemented in the State of Ecuador in 2008 in regard to democratization of access to higher education, being understood as a right that reduces the existing gaps between men and women, ethnicities and quintiles; for this purpose, a mixed methodology is used as the starting point and, using a qualitative analysis, a review of the main legal instruments regulating higher education in Ecuador was performed, along with specific articles related to this subject. For quantitative methodology, the starting points were reports of the National Information System (SNI) in regards to net rate of enrollment in higher education, managed by the National Secretariat of Planning in order to perform a descriptive analysis on its evolution in gender, ethnicity and registration quintiles. Among the main results obtained, it was determined that the gratuity policy did have a positive effect for access to higher education for men, women, African-Ecuadorian and indigenous peoples and, for quintiles 1, 2 and 3 until year 2011, a noticeable increase was seen in nationwide net rate of enrollment with 4.95 percentile points between 2007 and 2011, until the meritocracy policy entered in force in 2012.